Greedy bones - Haines, Carolyn (New York : Minotaur Books, 2009)
From feuding scientists to ailing locals, Sarah Booth Delaney finds no shortage of bad blood coursing through the little town of Zinnia, Mississippi, as she drops everything to stop an outbreak of boll weevils and save the only place she's ever been able to call home.
edited hb 2015-06-16